Cultural Significance of the Tradition of "Mandi Ke Aek" in Mersam Village, Mersam District, Batanghari District: Ethnolingusitic Study - Mahdi Bahar; Julisah Izar; Hartati; Fatonah; Dini Meidiyanti Putri (JOLADU: Journal of Language Education, 2023)
In Ethnolinguistic science, we are invited to see how the process of forming a culture and we are also invited to understand the cultural meanings contained in that culture or tradition. This research was conducted with the aim of knowing how the cultural procession contained in the tradition of "Mandi ke Aek" in Mersam Village, Mersam District, as well as to find out the cultural meanings contained in the icons, activities, and languages contained in the tradition. The research method used is a qualitative ethnographic approach with 4 stages, namely: (1) development of basic recognition of objects, (2) grouping and defining the types of activities to be studied, (3) focusing on culture in search, (4) moving backwards to look back at the general theory of culture that is researched and studied with specific cases. As for data collection techniques by means of interviews and field observations. Which after the data has been collected, researchers define, group, and explain the meanings contained. So that the results of the study were obtained as many as 46 data that have cultural meaning. The 46 data, consisting of 21 Icons, 16 activities, and 9 languages. And of the 46 data, it is known to have each function and purpose to be achieved from the implementation of the tradition.